Elevated expression of eukaryotic translation initiation factor 4E is associated with proliferation, invasion and acquired resistance to erlotinib in lung cancer - Li, Yikun (Landes Bioscience, 2012)
Eukaryotic translation initiation factor 4E (eIF4E) is the rate-limiting factor for cap-dependent translation initiation, which is known to regulate oncogenesis. Elevated eIF4E and its negative impact on prognosis in human non-small cell lung cancer (NSCLC) have been reported previously. However, its potential as a therapeutic target and role in regulation of sensitivity to EGFR inhibitors is an area of ongoing investigations. In this study, we detected increased levels of eIF4E in 16 human NSCLC cell lines compared with their normal bronchial epithelial cells. Consistently, human tissue array analysis showed that eIF4E expression was significantly higher in human NSCLC tissues than normal tissues. Inhibition of eIF4E using eIF4E siRNA inhibited the growth and invasion of NSCLC cells. These data suggest that eIF4E overexpression plays a crucial role in positive regulation of the growth and invasion of NSCLC cells. By proteomics, we found that eIF4E levels were elevated in erlotinib-resistant cell lines compared with the sensitive parental cell line. In agreement, assembly of the eIF4F cap complex and several oncogenic proteins regulated by the cap-dependent translation mechanism, were also increased in erlotinib-resistant cells. Thus, erlotinib-resistant cells exhibit elevated eIF4E expression and cap-dependent translation. Inhibition of eIF4F with different means (e.g., gene knockdown) downregulated c-Met expression and partially restored cell sensitivity to erlotinib, suggesting that elevated eIF4E contributes to development of erlotinib resistance, likely through positive regulation of c-Met expression. Taken together, we suggest that elevated eIF4E in NSCLC cells is associated with proliferation, invasion and acquired erlotinib resistance.